The interactions between wheat starch and Mesona chinensis polysaccharide: A study using solid-state NMR. (30th June 2019) - Yuris, Anynda; Hindmarsh, Jason; Hardacre, Allan Keith; Goh, Kelvin Kim Tha; Matia-Merino, Lara
Highlights: Wheat starch and Mesona chinensis polysaccharide (MCP) interacts at molecular level. The proton population of starch and MCP can only be distinguished at <5 nm. MCP was found to increase the flexibility of carbon 6 of the glucan polymer. Carbon 6 of the glucan polymer was thought to be the site of starch-MCP interaction. Abstract: The interaction between wheat starch and Mesona chinensis polysaccharide (MCP) was found to change the molecular mobility of the water and carbohydrate populations in starch-MCP gels, when measured using proton and carbon nuclear magnetic resonance relaxation methods. The starch and MCP mobilities appeared similar at a micron scale. However, at a distance of less than 5 nm could they be detected as having separate mobility states, indicating close interaction between the starch and MCP. The carbon-6 of the starch glucan monomer was observed to have the largest mobility change in the presence of MCP. Two mobility populations of carbon-6 were observed, possibly corresponding to the carbon-6 in the linear chains of both amylose and amylopectin, and another to the carbon-6 involved in the branching of amylopectin. The change in the mobility of one of the carbon-6 populations indicates an increase in molecular freedom of movement in the presence of MCP.